Bridging the Gap Between UK Government Strategic Narratives and Public Opinion/Behavior: Lessons From COVID-19 - Dagnall, Neil; Drinkwater, Kenneth Graham; Denovan, Andrew; Walsh, R. Stephen (Frontiers in Communication, 2020)
In the UK, there exists a significant ‘action gap’ between Government advice on measures necessary to counter the threat of COVID-19, and the behaviour of a significant minority of the population. There are several reasons for this disconnect, such as lack of message potency (i.e., credibility and congruence), inflexible/habitual behaviour patterns, prevailing beliefs (i.e. vulnerability to, and seriousness of COVID-19), and individuals valuing personal concerns above general public health. For official messages to be effective and advice adhered to, strong, coherent ‘strategic narratives’ are required. This article looks at prevailing COVID-19 government discourses, highlights important inconsistencies, and considers factors that facilitate and create barriers to the adoption of government public health directives. This includes deliberation of factors that enhance source impact, diminish the influence of message content, and the negative consequences of contrary information. Accordingly, this perspective will propose a framework for providing a unifying strategic narrative on COVID-19, one that is most likely to maximise the impact of key messages and promote effective behaviour change. This will place an emphasis on engaging the full range of actors and consider ways of reducing the efficacy of false information. The article will also provide recommendations that will help to increase the reception of government policy and suggest how strategic narratives can harness the drivers of behavioural change needed to meet challenges such as COVID-19.